(untitled) (Journal of the College of Basic Education, 2026)
This research examines the syntactic and rhetorical interpretation of the Qur’anic reading of Imam Ibn ʿĀmir al-Shāmī in the verse: Thus, the killing of their children was made appealing to many of the polytheists(( (Qur’an 6:137(The study focuses on the phenomenon of inserting a syntactic separator between the genitive construction (iḍāfa), a subtle grammatical issue that has long sparked debate among grammarians and exegetes. The research highlights the significance of the mutawātir Qur’anic readings as authoritative linguistic evidence, which serve not only as sources for grammatical rules but also as grounds for expanding them, rather than being subject to later grammatical restrictions. Using a descriptive-analytical approach, the study traces the views of major grammarians such as Ibn Hishām, Ibn Jinnī, and al-Zamakhsharī, alongside the defenses provided by leading Qur’anic reciters such as Ibn al-Jazarī. The research concludes that the separation found in this reading is neither anomalous nor irregular; instead, it is grounded in a valid rhetorical and syntactic logic that foregrounds the verb “killing” (qatlu) to intensify semantic impact, followed by the delayed mention of “their children” to create emphasis and rhetorical suspense. The study affirms that Qur’anic readings represent a superior linguistic reference, upon which rules are based rather than measured against, thus broadening the understanding of Qur’anic grammar and stylistics.